Nutrient Limitation Causes Differential Expression of Transport- and Metabolism Genes in the Compartmentalized Anammox Bacterium Kuenenia stuttgartiensis - Smeulders, Marjan J.; Peeters, Stijn H.; van Alen, Theo; de Bruijckere, Daan; Nuijten, Guylaine H. L.; op den Camp, Huub J. M.; Jetten, Mike S. M.; van Niftrik, Laura (Frontiers in Microbiology, 2020)
Anaerobic ammonium-oxidizing (anammox) bacteria, members of the ‘Candidatus Brocadiaceae’ family, play an important role in the nitrogen cycle and are estimated to be responsible for about half of the oceanic nitrogen loss to the atmosphere. Anammox bacteria combine ammonium with nitrite and produce dinitrogen gas via the intermediates nitric oxide and hydrazine (anammox reaction) while nitrate is formed as a by-product. These reactions take place in a specialized, membrane-enclosed compartment called the anammoxosome. Therefore, the substrates ammonium, nitrite and product nitrate have to cross the outer-, cytoplasmic- and anammoxosome membranes to enter or exit the anammoxosome. The genomes of all anammox species harbor multiple copies of ammonium-, nitrite- and nitrate transporter genes. Here we investigated how the distinct genes for ammonium-, nitrite- and nitrate- transport were expressed during substrate limitation in membrane bioreactors. Transcriptome analysis of Kuenenia stuttgartiensis planktonic cells showed that four of the seven ammonium transporter homologs and two of the nine nitrite transporter homologs were significantly upregulated during ammonium-limited growth, while another ammonium transporter- and four nitrite transporter homologs were upregulated in nitrite limited growth conditions. The two nitrate transporters were expressed to similar levels in both conditions. In addition, genes encoding enzymes involved in the anammox reaction were differentially expressed, with those using nitrite as a substrate being upregulated under nitrite limited growth and those using ammonium as a substrate being upregulated during ammonium limitation. Taken together, these results give a first insight in the potential role of the multiple nutrient transporters in regulating transport of substrates and products in and out of the compartmentalized anammox cell.